Fruit and vegetable peels as alternative feed for sustainable poultry production: A solution for small-scale farms in central and southern Ethiopia - Getahun, A.; Kechero, Y.; Yemane, N.; Dessie, Tadelle; Esatu, Wondmeneh (Wiley, 2026)
Sustainable poultry production is essential for small-scale farmers in resource-limited regions such as central and southern Ethiopia, where feed costs account for 60%–70% of production expenses. This study evaluates fruit and vegetable peels including potato, banana, avocado, mango, cassava, papaya, beetroot and pumpkin as alternative feed ingredients for sustainable poultry nutrition by analysing their nutritional profiles and anti-nutritional factors (ANFs). Data from 360 households across Hadiya, Wolaita and Gamo zones revealed potato peel as the most utilized (27.5%, p < 0.05), exhibiting the highest metabolizable energy (3.17 Mcal/kg DM) and crude protein (7.33%, p < 0.001). Banana peel ranked second (18.89%) with moderate protein (5.5%) and high potassium (482 mg/100 g, p < 0.001), while cassava peel showed exceptional calcium (178.7 mg/100 g) and phosphorus (97 mg/100 g) content (p < 0.001) but required detoxification due to elevated oxalates (283.3 mg/100 g) and tannins (0.7 mg/100 g, p < 0.001). Nutritional analyses revealed significant variations in ash content (4.26%–7.83%), crude fibre content (5.7%–18.3%) and mineral composition across peels (p < 0.001). Despite regional adoption differences (p < 0.05), all peels showed potential as sustainable, cost-effective feed alternatives that align with circular economy principles. In conclusion, pumpkin peel exhibited the highest overall nutritional value among the evaluated fruit and vegetable peels. The study further underscores the importance of applying appropriate processing methods to reduce ANFs, while also highlighting the environmental and economic benefits of utilizing locally available agro-wastes as sustainable poultry feed resources. Further research should optimize detoxification techniques and inclusion levels to maximize poultry productivity and safety.